The Inauguration Ceremony of Ahmad Shawqi as Prince of Arab Poets in Cairo, 1927 - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2023)
Ahmad Shawqi became a member of the Senate in 1924 and was named the ‘Prince of Poets’ in 1927. This was the year that the second edition of his poetry collection, Al-Shawqiyyat, was published. The first edition was published in 1898, and on the occasion of the issuance of the second edition, a number of ceremonies honouring the poet were held in his behalf. This pledge of allegiance constituted a national event par excellence. The ceremony was attended by King Fu'ad, Prime Minister Sa'ad Zaghloul, and a large group of Arab visitors. Bahrain participated by sending a small golden palm tree, which was donated by its emir to the Prince of Poets. The ‘Princedom of Arab Poetry’, began with the pledge of allegiance to Ahmad Shawqi, during a special ceremony on 29 April 1927 in the presence of a group of Arab poets. This group was led by Hafeth Ibrahim, Shawqi’s competitor, to confirm that Shawqi was undoubtedly the highest poet among his peers at the time, and he has remained distinguished in the Arab consciousness to the present day, despite the rise of other good poets and many poetic movements.